2004
DOI: 10.1677/jme.0.0330099
|View full text |Cite
|
Sign up to set email alerts
|

YY1 binding within the human HSD3B2 gene intron 1 is required for maximal basal promoter activity: identification of YY1 as the 3beta1-A factor

Abstract: The oxidation and isomerization of 3 -hydroxy-5-ene steroids into keto-4-ene steroids, a pivotal step in the synthesis of all hormonal steroids, is catalyzed by several isoforms of 3 -hydroxysteroid dehydrogenase. In humans, two highly homologous isoforms exist, type I expressed by the HSD3B1 gene in peripheral tissues, and type II expressed by the HSD3B2 gene in steroidogenic organs. Previously, it was shown that the HSD3B1 gene 3 1-A element, encompassing 24 nucleotides of intron 1 not perfectly conserved be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(51 reference statements)
2
3
0
Order By: Relevance
“…We further found that YY1 suppressed FXR expression via interaction with the YY1 binding site in the first intron of the FXR gene. Similar regulatory models were also reported previously regarding CD21 and HSD3B2 expression regulated by YY1 29 30…”
Section: Discussionsupporting
confidence: 89%
“…We further found that YY1 suppressed FXR expression via interaction with the YY1 binding site in the first intron of the FXR gene. Similar regulatory models were also reported previously regarding CD21 and HSD3B2 expression regulated by YY1 29 30…”
Section: Discussionsupporting
confidence: 89%
“…Because artificial "promoterreporter" assays allow the use of chosen parts of promoters only, essential elements, which are modulated by pioglitazone, may be missed. Recently, a specific intronic sequence of the HSD3B gene has been reported to be important for basic promoter activity of both HSD3B2 and HSD3B1 genes (Foti and Reichardt, 2004), corroborating our hypothesis. Alternatively, pioglitazone might affect the stability of HSD3B2 mRNA.…”
Section: Downloaded Fromsupporting
confidence: 90%
“…YY1 has been implicated in the regulation of a large number of mammalian genes [41]. Moreover, YY1 was also found to affect gene expression by interaction with binding motifs positioned downstream of the transcriptional start site, within the coding region [42] or the intron sequences of target genes [43], [44].…”
Section: Discussionmentioning
confidence: 99%